Angioplasty and angiorrhaphy efficiency in renal transplantation scenarios with multiple arteries and veins - Hung Quoc Doan; Tuan Minh Nguyen; Nghia Quang Nguyen; Lu Huu Pham; Khai Viet Ninh (Asian Journal of Surgery, 2022)
Objective: To evaluate post-transplant renal perfusion and vascular complications of renal transplantation in patients with the end-stage renal disease (ESRD) operated in the presence of multiple blood vessels at Viet Duc University Hospital. Methods: A non-controlled interventional study was performed prospectively and retrospectively between January 2012 and June 2018. The study sample includes 84 patients who underwent live donor renal transplantation in the presence of multiple arteries (RAs) and veins (RVs) at Viet Duc Hospital. The surgical procedure comprised of end-to-side anastomosis to the recipient's external iliac artery/vein, gun barrel anastomosis of two RAs/RVs, anastomosis of the small RA/RV to the main RA/RV, anastomosis of the polar artery to the inferior epigastric artery, small artery constriction, and their combinations. Results: On clamp removal, 94% of the transplanted kidneys were solid and evenly pink, 3.6% had bruises due to small artery constriction, 1.2% were poorly perfused due to vasoconstriction, and 1.2% had renal artery branches occluded by blood clots and required anastomosis re-opening. All kidneys began to produce urine on the operating table. Conclusion: A high success rate of renal transplantation in the presence of multiple blood vessels requires that surgeons have sufficient experience and use a combination of angioplasty and angiorrhaphy techniques.